Exploring physical activity preferences and motivation in long-term cardiac prevention: An Austrian cross-sectional survey. - Hannah McGowan; Johanna Gutenberg; Veronika Leitner; Kathrin Mühlhauser; Aliz Breda; Michael Fischer; Sebastian Globits; Vincent Grote; David Kiesl; Karl Mayr; Michael Muntean; Andrea Podolsky; et al. (PLoS ONE)
Cardiac rehabilitation (CR) patients often do not sustain physical activity (PA) behaviour in the long run, once they progress into a self-management stage of secondary prevention. This study aimed to explore former CR patients' PA preferences, determinants (i.e., influencing factors) and motivation for sustained PA engagement. We conducted a cross-sectional multi-centre survey using an original questionnaire based on prior qualitative interviews with cardiac patients. Five CR centres in Austria posted 500 questionnaires to former CR patients who had completed CR approximately three years prior, and 117 patients (23%) responded. Descriptive analysis was used to analyse closed-ended questions, and self-determination theory (SDT) was applied as a qualitative framework to analyse open-ended questions concerning motivation for PA engagement. Patients were generally physically active, but the majority (75.3%) did not fulfil the World Health Organisation's recommendations for aerobic PA and muscle strengthening. Most patients preferred being physically active outdoors (70%), engaging in aerobic-related (95%), individual and non-competitive exercises, with cycling (52%), walking (32%) and hiking (25%) among the most popular activities. Main determinants of PA were health, pain and motivation for 80%, 68%, 67% of patients, respectively. A subset of patients (77%) expanded on their motivations behind PA. According to SDT, most reasons (90%) were regulated by autonomous motivation (either extrinsically autonomously-regulated or intrinsic motivation) and stemmed mostly from health-related goals (e.g., fitness, general health, weight control), future quality-of-life aspirations (e.g., self-sufficiency in old age, presence for loved ones, preserving mobility) and enjoyment of PA. Patients' responses underscore the importance of promoting not only general PA, but also muscle strengthening training in CR interventions to maximise optimal health benefits. Our data further suggest that interventions which are aligned to patients' health goals and foster autonomous motivation may be particularly beneficial in increasing adherence to PA in the long-term.